Pengembangan Kepribadian Anak Melalui Pendidikan Karakter di Madrasah Ibtidaiyah - Rifa’i, Muhammad Rizal; Hafidhoh, Noor (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Character education is an important aspect for the next generation. It is not enough for an individual to only be given the provision of learning in terms of mere intellectuality but also in terms of morals and spirituality, character education should start early, especially in educational institutions, namely at the elementary level or MI. Habituation in the school/madrasah environment, children will learn from their immediate environment, this is what we must then be more aware of to create a positive school or madrasa culture and culture for the development of the character of students. Based on the object of study, this research includes research that is literal or library in nature (library research), which is a research conducted by collecting data, information and various other data contained in the literature. The aim is to find out the implementation of the basic concepts of character education whose results through various additional or development programs (outside the regular learning process) organized by the school or madrasa will support the realization of the character and character of students.